2018
DOI: 10.1001/jamacardio.2018.1813
|View full text |Cite
|
Sign up to set email alerts
|

Association of Out-of-Pocket Annual Health Expenditures With Financial Hardship in Low-Income Adults With Atherosclerotic Cardiovascular Disease in the United States

Abstract: One in 4 low-income families with a member with ASCVD, including those with insurance coverage, experience a high financial burden, and 1 in 10 experience a catastrophic financial burden due to cumulative out-of-pocket health care expenses. To alleviate economic disparities, policy interventions must extend focus to improving not only access, but also quality of coverage, particularly for low-income families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 41 publications
3
75
0
Order By: Relevance
“…15 Another study evaluated household level catastrophic health expenditures for acute myocardial infarction (MI) and stroke in the United States among those uninsured during 2008-2012. 22 Median hospital charges were $53,000 for acute MI and $31,000 for stroke. Using an indicator of household disposable income (ie, net of subsistence expenses), researchers estimated the rates of catastrophic health expenditure (ie, spending more than Economic Dimensions of Health Inequities -Engelgau et al a threshold of 40% of the household disposable income) and found roughly 80% of those with acute MI and 75% with stroke were above this threshold, suggesting severe personal and family financial distress.…”
Section: Economic Burden Of Heath Inequitiesmentioning
confidence: 99%
“…15 Another study evaluated household level catastrophic health expenditures for acute myocardial infarction (MI) and stroke in the United States among those uninsured during 2008-2012. 22 Median hospital charges were $53,000 for acute MI and $31,000 for stroke. Using an indicator of household disposable income (ie, net of subsistence expenses), researchers estimated the rates of catastrophic health expenditure (ie, spending more than Economic Dimensions of Health Inequities -Engelgau et al a threshold of 40% of the household disposable income) and found roughly 80% of those with acute MI and 75% with stroke were above this threshold, suggesting severe personal and family financial distress.…”
Section: Economic Burden Of Heath Inequitiesmentioning
confidence: 99%
“…First, as shown in Table 1 of the article by Mohanan et al, 2 patients with AMI who had health insurance in India were unique in that their household income was only half of those with insurance-a significant contrast with the United States, where access to health insurance is a sign of affluence. 3 The insurance programs in India, particularly the Rashtriya Swasthya Bima Yojana, a tax-financed national insurance program, however, have mainly focused on providing coverage for inpatient care for individuals and family members below the poverty line. 2 The program, which as of 2016 covered more than 160 million people, has incentivized an investment in tertiary or specialized Second, the degree of financial protection offered by insurance for patients with AMI is unclear.…”
mentioning
confidence: 99%
“…In addition to the adequacy and value of care achieved by the insured in India, it is imperative to evaluate if patients are burdened by medical bills beyond their means, if they have forgone care or treatment because of costs, and how treatment of chronic conditions are pursued 6. The costs of medications and outpatient care represent a substantial burden in this patient group with cardiovascular disease but remain understudied 3. The association of these financial stressors with patient health and well-being are also underappreciated.Finally, as we encourage more comprehensive insurance offering financial protection from longterm disease management beyond acute health care events, we feel there is an urgent need for concurrent investment in programs that focus on prevention to counter the growing financial strains on health systems.…”
mentioning
confidence: 99%
“…3 Less access to primary care may result in patients returning to the hospital when problems arise and the high financial burden of healthcare expenses may result in low income adults to not seeking care till the last minute. 4 The Hospital Readmissions Reduction Program 5 has raised awareness of readmissions to health services and administrators that may result in better recording, monitoring and identification of readmissions. It is possible there is an increasingly elderly population who presents to hospital and these patients often have multiple co-existing illness that increase the risk of unplanned readmissions.…”
Section: Discussionmentioning
confidence: 99%